Original paperPort-wine stains - Iljin, Aleksandra; Siewiera, Ireneusz; Kruk-Jeromin, Julia (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2010)
Introduction : Port-wine stains are the most common vascular malformations, occurring mostly on the head and neck, which in comparison with vascular tumours do not involute spontaneously. They cause aesthetic and therapeutic problems. Treatments of choice are laser therapy and in special cases surgery. The cause of port-wine stains’ formation is disturbances of morphogenesis, probably as a consequence of external and genetic factors. Aim: To analyse cases with these lesions considering pathomorphology, coexistence of congenital syndromes and assessment of surgical treatment. Material and methods : The study group consisted of 187 patients with port-wine stains aged 0.5-70 years treated in the Department of Plastic Surgery, Medical University of Lodz in the years 1990-2009. We assessed location and morphology of the lesions, coexistence of other congenital anomalies and pathogenesis. Results : In our group women were affected twice as often as boys. Port-wine stains in 70% were situated unilaterally on the face and neck, particularly in dermatome V2. We found Klippel-Trenaunay syndrome in two patients and Sturge-Weber syndrome in one case. Surgical management included excision of the lesions together with local plasty or skin grafts. Postoperative results in the studied group were satisfied. Conclusions : More frequent occurrence of port-wine stains in women was observed. Most often distribution of the lesion was the face and neck in the area supplied by the maxillary branch of the trigeminal nerve. It was not possible to establish the aetiopathogenesis. The choice of surgical technique to liquidate port-wine stains depends on location, size and deformity surrounding area. Usually local flaps or skin grafts are used. In small defects the best aesthetic results have been obtained when we used full-thickness skin grafts from the posterior conchal surface and from the post-auricular area. Less invasive laser therapy is not 100% effective. Efficiency of this method depends on location, and morphology of the lesion necessitating repeated exposures, which is not completely covered by the NHS.